A RESEARCH ON POLICIES FOR GREEN ECONOMY IN DEVELOPED AND DEVELOPİNG COUNTRİES WİTHİN THE SCOPE OF SUSTAINABLE DEVELOPMENT - Ömer Faruk GÜLTEKİN; Betül ERENOĞLU (Challenges of the Knowledge Society)
With the increasing population since the existence of mankind technology has developed the use of resources which increased with development of technology and production and environmental destruction has been the result of this. The process of environemntal degredation, especially after the industrial revolution, was accelerated since the Second World War and become a global problem. It had a more important role in terms of sustainable development of intellectual property in arrangement to use resources efficiently and effectively to reduce the environmental damage and to increase the social wealth and to leave a clean world in the future generations. The green economiy thought, which in the light of sustainable development compress, expresses reconstruction of environmental activities differently in the thought of mainstream economy on the basis of green neworder eceonomics. The objective of this study is to investigate the environmental politicl inclusion of the green ecenomy is and examine regional and global results individually and in groups on behalf of both developed and developing countries